Patient expectations and experiences with loop electrosurgical excision procedure in inpatient and outpatient settings. (28th June 2022) - Ooi, Sara; Eskaroos, Mary Anne; Pather, Selvan; Carter, Jonathan; Saidi, Samir
Abstract : Background: Loop electrosurgical excision procedure (LEEP) for high‐grade squamous intraepithelial lesion is performed in both an inpatient setting under general anaesthesia and an outpatient setting under local anaesthesia. Efficacy and safety are comparable and outpatient LEEP may save time and cost in the Australian setting. Aims: We aim to compare patient satisfaction with inpatient LEEP compared to outpatient LEEP for Australian best practice. Materials and Methods: This was a prospective quantitative and qualitative cohort study. An online questionnaire was sent to patients undergoing inpatient and outpatient LEEP to assess satisfaction with the procedure. Further histopathological and demographic data were also collected from the medical records. Groups were compared using Fischer's exact test and pain scores were compared using non‐parametric tests. Results: Ninety‐three outpatients and 52 inpatients responded to the survey. No difference was found between groups with regard to rate of positive histopathological margins or number of passes required. Outpatients found the procedure to be more convenient than inpatients ( P = 0.007), and experienced more pain during the procedure than the inpatient group ( P < 0.001). There was no significant difference in pain scores following the procedure or post‐procedure anxiety. Conclusions: Outpatient LEEP is an acceptable and well‐tolerated procedure, comparable to inpatient LEEP. Regardless of the option chosen, patients are highly likely to be satisfied with their choice. Increased efforts should be made to reduce pre‐procedural anxiety, which may in turn reduce expectations and experiences of pain.